2023
DOI: 10.3389/fnbeh.2022.954319
|View full text |Cite
|
Sign up to set email alerts
|

Negative and positive allosteric modulators of the α7 nicotinic acetylcholine receptor regulates the ability of adolescent binge alcohol exposure to enhance adult alcohol consumption

Abstract: Rationale and Objectives: Ethanol acts directly on the α7 Nicotinic acetylcholine receptor (α7). Adolescent-binge alcohol exposure (ABAE) produces deleterious consequences during adulthood, and data indicate that the α7 receptor regulates these damaging events. Administration of an α7 Negative Allosteric Modulator (NAM) or the cholinesterase inhibitor galantamine can prophylactically prevent adult consequences of ABAE. The goals of the experiments were to determine the effects of co-administration of ethanol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…Maldonado-Devincci et al [ 67 ] indicated IG administration of 1.5, 3.0, or 5.0 g/kg ethanol in 4 days intervals (PND 28–31, PND 35–38, and PND 43–45) increased ethanol consumption in young adulthood (PND 60–69) in both male and female Sprague-Dawley (SD) rats, an effect more prominent in male compared to female animals. Intermittent IG ethanol exposure (PND 28–48; 2 days on/2 days off) treatment in male and female P rats resulted in increased adult ethanol consumption (PND 90+) during both operant acquisition and relapse drinking conditions [ 68 , 69 ]. In contrast, repeated gavage (every 8 h for 2 days: 6 treatments total) during adolescence (PND 30–32) decreased ethanol consumption in adulthood in Sprague Dawley rats [ 70 ].…”
Section: Adolescent Intermittent Ethanol (Aie) Exposure Effects Adult...mentioning
confidence: 99%
See 3 more Smart Citations
“…Maldonado-Devincci et al [ 67 ] indicated IG administration of 1.5, 3.0, or 5.0 g/kg ethanol in 4 days intervals (PND 28–31, PND 35–38, and PND 43–45) increased ethanol consumption in young adulthood (PND 60–69) in both male and female Sprague-Dawley (SD) rats, an effect more prominent in male compared to female animals. Intermittent IG ethanol exposure (PND 28–48; 2 days on/2 days off) treatment in male and female P rats resulted in increased adult ethanol consumption (PND 90+) during both operant acquisition and relapse drinking conditions [ 68 , 69 ]. In contrast, repeated gavage (every 8 h for 2 days: 6 treatments total) during adolescence (PND 30–32) decreased ethanol consumption in adulthood in Sprague Dawley rats [ 70 ].…”
Section: Adolescent Intermittent Ethanol (Aie) Exposure Effects Adult...mentioning
confidence: 99%
“…Administration of an α7 nAChR negative allosteric modulator (NAM) dehydronorketamine (DHNK) 2 hours before AIE exposure (PND 28–48) prevented the increase of ethanol consumption during acquisition and relapse drinking during adulthood in both male and female P rats [ 68 ]. A subsequent study reported that SB-277011-A, an α7 nAChR NAM and a D3 antagonist, could also suppress ethanol consumption during acquisition and relapse drinking in female P rats [ 69 , 148 ]. In contrast, to α7 nAChR NAMs, activation of the α7 nAChR during adolescence appears to have the opposite effect on ethanol consumption in adulthood.…”
Section: Potential Pharmacotherapies To Mitigate the Effects Of Binge...mentioning
confidence: 99%
See 2 more Smart Citations